PENGARUH PERSUASI ATAS PREFERENSI KLIEN DAN PENGALAMAN AUDIT TERHADAP PERTIMBANGAN AUDITOR DALAM MENGEVALUASI BUKTI AUDIT - Arum, Enggar Diah Puspa (UI Scholars Hub, 2008)
The purpose o f this research is to analyze whether the persuasiveness o f client preferences and audit experiences have effect toward the auditors judgem ent in evaluating audit evidences both partially and simultaneously Survey in this study is applied on 62 auditors who work at public accounting firm s in Bandung by using a multiple linier regression analysis. The result indicates that the persuasiveness o f client preferences and audit experiences have a significant positive effect to the auditor s judgem ent in evaluating audit evidences both partially and simultaneously. The future research is suggested to examine other variables, such as: task complexity, gender, and conflicting fe e with extended research subject. Beside that, the future research is suggested to develop an experimental method so that the respondent behavior differences fo r each task can appear clearly.